PENGARUH RISIKO KREDIT, PROFITABILITAS, LIKUIDITAS, DAN EFISIENSI USAHA TERHADAP KECUKUPAN MODAL PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - NATASIA, RIZKY (Jurnal Akuntansi AKUNESA, 2015)
This study was aimed at examining the effect of credit risk, profitability, liquidity, and business efficient of banks listed in Indonesian Stock Exchange at period 2010-2014 to capital adequacy. The technique of data analysis used was multiple linear regression analysis which was preceded by classic assumption testing and then followed by regression analysis and model testing that consisted of determination coefficient analysis, simultaneous testing ( F-test), and partial testing (t-test) using SPSS 22 program.Result of the research shows that credit risk variable which measured by NPL, and profitability (with ROA) take effect towards capital adequacy. While, liquidity variable which measured by LDR and business efficient (with BOPO) have no effect towards capital adequacy of banks listed in Indonesian Stock Exchange at period 2010-2014. Keywords : Credit risk, profitability, liquidity, business efficient, capital adequacy